Features of theoretical and methodical approaches to rental fee definition in foreign countries - Zharylkasynovich, Abdraiym Bakytzhan Bakytzhan; Zhussupbekovna, Suleimenova Saule Saule; Altynbekovna, Saimova Sholpan Sholpan (Teisė, 2012)
In the developed system of land use fees the rent in the greatest measure, in comparison with other types of a payment, represents itself as a market indicator. This article is devoted to the theoretical and methodical analysis of rental fee for a land in foreign countries. Authors give special attention to studying of the current legislation of foreign countries in this area, identification of its gaps and shortcomings, development of recommendations and the offers directed on improvement of the existing land legislation.